ACCESS TO HIGHER EDUCATION: SOURCE OF GRADUATE EMPLOYABILITY AND WELLBEING (Journal of Education and Educational Development, 2020)
Access to higher education has been the subject of considerable debate among policy makers and academicians. But the concept lacks empirical evidence regarding its impact upon students and societal outcomes. This study provides empirical answer to the research question: how do access to higher education and teachers’ support relate to graduates’ self-perceived employability and psychological wellbeing? The data were collected from 520 students of bachelors and master’s programs in rural campuses of an oldest University of Pakistan and analyzed through Structural Equation Modelling (SEM) using AMOS and SPSS software. Results reveal that access to higher education and teachers support are positively related with selfperceived employability of graduating student with little or no difference among gender. Whereas, teachers support also contributes to psychological wellbeing of the students. The impact of access to higher education on psychological wellbeing was insignificant. This study provides implications for universities, policy makers, and human resource management professionals regarding enhancement of graduate employability.